External Perceptions and Indonesia's Leadership Role in Indo-Pacific Maritime Affairs - Muhammad Samy (Universitas Diponegoro, 2024)
Bahasa Indonesia:Visi Indonesia untuk menjadi pemimpin kawasan dalam hal kemaritiman telah menjadi isu yang diperdebatkan oleh akademisi maupun politis. Beberapa akademisi berargumen bahwa Indonesia tidak dapat menjalankan peran sebagai pemimpin kawasan dalam hal kemaritiman karena lemahnya kehendak politik, kurangnya sumber daya, serta lemahnya persepsi diri sebagai pemimpin. Dengan menggunakan kerangka analisis teori peran, tulisan ini menghadirkan jawaban alternatif terhadap isu kepimpinan regional Indonesia dalam hal kemaritiman. Tulisan ini berargumen bahwa Indonesia memang memandang diri sebagai pemimpin kawasan dalam hal kemaritiman, namun masalah dalam menjalankan kepemimpinan tersebut terletak pada lemahnya persepsi eksternal atas kepemimpinan Indonesia.English:Indonesia’s aspirations of becoming a leader in regional maritime affair has become a point of contention among scholars and politicians alike. Many scholars argue that Indonesia is unable to effectively take on the role of a regional leader in maritime affairs due to weak political will, lack of resource, or lack of self-perception as both a maritime state and regional leader. Building upon the analytical framework of role theory, this paper brings forth a different answer to the question of Indonesia’s leadership in regional maritime affairs. This paper argues that Indonesia does view itself as a maritime state and regional leader, and that the issue of Indonesia’s leadership is rooted in the lack of external perception towards Indonesia’s leadership in regional maritime affairs.